The effect of chronic neuroglycopenia on resting state networks in GLUT1 syndrome across the lifespan. Issue 2 (11th November 2019) - Vaudano, Anna Elisabetta; Olivotto, Sara; Ruggieri, Andrea; Gessaroli, Giuliana; Talami, Francesca; Parmeggiani, Antonia; De Giorgis, Valentina; Veggiotti, Pierangelo; Meletti, Stefano
Abstract: Glucose transporter type I deficiency syndrome (GLUT1DS) is an encephalopathic disorder due to a chronic insufficient transport of glucose into the brain. PET studies in GLUT1DS documented a widespread cortico‐thalamic hypometabolism and a signal increase in the basal ganglia, regardless of age and clinical phenotype. Herein, we captured the pattern of functional connectivity of distinct striatal, cortical, and cerebellar regions in GLUT1DS (10 children, eight adults) and in healthy controls (HC, 19 children, 17 adults) during rest. Additionally, we explored for regional connectivity differences in GLUT1 children versus adults and according to the clinical presentation. Compared to HC, GLUT1DS exhibited increase connectivity within the basal ganglia circuitries and between the striatal regions with the frontal cortex and cerebellum. The excessive connectivity was predominant in patients with movement disorders and in children compared to adults, suggesting a correlation with the clinical phenotype and age at fMRI study. Our findings highlight the primary role of the striatum in the GLUT1DS pathophysiology and confirm the dependency of symptoms to the patients' chronological age. Despite the reduced chronic glucose uptake, GLUT1DS exhibit increased connectivity changes in regions highly sensible to glycopenia. Our results may portrait the effect of neuroprotective brain strategy to overcome the chronic poor energy supply during vulnerable ages.